A Study on Self-Cleaning Silk Fabric Modified by Photoactive Nanocomposites TiO2/SiO2 - Tran, Nguyễn Tú Uyên; Bui, Mai Hương; Hoang, Thanh Thảo; Le, Trung Tín (Journal of Technical Education Science, 2023)
Textile and their end products constitute the world’s second largest industry. Among natural fabrics, silk is one of the best and has been used for thousands of years but it also not easy-to-care materials. Sefl-cleaning represent a remarkable step forward in functionalized treatment for valued materials with a high potential for commercialization. In this study, silk fabrics were functionalised using TiO2/SiO2 nanocomposites through sol–gel coated method. Titanium terta isopropoxide (TTIP) and nano SiO2 were employed as precursors of TiO2 and SiO2. The self-cleaning function of silk fabrics were analysed based on the removal of coffee stain under sunlight during 0 hours (h), 4 h, 8 h, 16 h and 20 h. The morphologies and effectiveness of the functionalized silk fabrics were observed by visual pictures, SEM and the CIE-LAB system for measuring color differences. The durability of the treatmented fabric and the self-cleaning function after 5 times of washings were also studied and discussed.